How Do Budget Deficits and Economic Growth Affect Reelection Prospects? Evidence from a Large Panel of Countries - Brender, Adi; Drazen, Allan (American Economic Review, 2008)
We test whether good economic conditions and expansionary fiscal policy help incumbents get reelected in a large panel of democracies. We find no evidence that deficits help reelection in any group of countries independent of income level, level of democracy, or government or electoral system. In developed countries and old democracies, deficits in election years or over the term of office reduce reelection probabilities. Higher growth rates over the term raise reelection probabilities only in developing countries and new democracies. Low inflation is rewarded by voters only in developed countries. These effects are both statistically significant and quite substantial quantitatively. (JEL D72, E62, H62, O47)